School organization in teaching performance in Educational Institution of Ayacucho - Yacca Poma, Heber (2024)
The aim of this research was to demonstrate the influence of school organization on campus teaching performance. With respect to the methodology, the research is experimental pre experimental design, sample is not probabilistic composed of 28 teachers from the three levels of the Equalization Program and Academic Reinforcement Holiday, "where the pre test and post test with record of observation of teaching performance was applied. To determine the normality of the data the statistician of the Shapiro-Wilk test at 95% confidence level and sample Wilcoxon statistic related to the process of verification of the hypothesis was used. In analyzing the results, it was determined that the calculated value of Z is -4.786 with the level of bilateral asymptotic significance: ρ = 0.000, a value which is lower than the critical region α = 0.05, then the null hypothesis is rejected and accepts the alternate; with a significance level of 5% and a confidence level of 95%. There is better teacher performance level after the development of the school organization. In conclusion, school organization affects educational performance Plantings Application "Guaman Poma de Ayala", Ayacucho (ρ = 0.000 <0.05, Z = -4.786).